Motives and Psychosocial Stressors in Parasuicides: Comparison of Self-Poisoners and Self-Cutters - Sorketti, E.A.; Zuraida, N.Z. (2007)
Understanding the motives or intentions and what premeditated deliberate selfharm is an important aspect in dealing with parasuicides. The aim of this study was to compare motives and psychosocial stressors between deliberate self-poisoners and self-cutters. Methods: 77 parasuicides consecutively admitted to University Malaya Medical Center (UMMC) were included in the study. They were assessed on socio-demographic profiles and clinical history. They also completed a questionnaire related to the suicide attempt such as the method, the motives and the psychosocial stressors. The motives and psychosocial stressor were than compared between those who had deliberately cut themselves (n=25) and those who had taken overdoses or poisons. Results: More patients who cut themselves than those who took overdoses said that they had wanted to die (56.7% versus 43.2%, p <0.001) and had wanted to punish themselves (66.7% versus 33.3%, p<0.01). More self-poisoners reported that they wanted to find out if someone really loved them (92.3% versus 7.7%, p<0.05) and had wanted to get some attention (87.0% versus 13.0%, p<0.01) as compared to selfcutters. 70% of the psychosocial stressors were due to relationship problems. There were significant differences between the motives for selfpoisoning and self-cutting. The often impulsive nature of these acts means that prevention should focus on encouraging alternative methods of managing distress, problem-solving and help-seeking before thoughts of self-harm develop.